Serum Estradiol levels during First Trimester of Pregnancy - Attiqa Khalid, Maria Gill, Sadia Nazir, Nazia Farooq, Faiqa Jabeen Naeem, Zaima Ali, Uzma Zafar, Hamid Javaid Qureshi, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate serum estradiol levels during first trimester. Methods: It was a descriptive, cross-sectional study, conducted on pregnant women between 18 to 35 years of age presenting during first trimester in obstetric unit of a tertiary care hospital in Lahore, Pakistan. Ultrasonography was done to confirm the viability of fetus. 53 women with nonviable pregnancy were included Group 1 and 28 women with viable fetus and no complication were included in Group 2. Those having any systemic illness or history of estrogen intake were excluded. Using aseptic measures, venous blood samples were taken, and serum was separated. Serum estradiol levels were measured by using immunoenzymometric assay (EIA). Median serum Estradiol levels were compared. Receiver operative characteristics (ROC) curve was plotted. Results: Median serum estradiol levels of women with viable pregnancy 150.49 ng/mL (71.01-393.75) were significantly higher than abortion group 9.96ng/mL (2.87-37.7). A cut off value 47.9ng/ml of serum estradiol is 82% sensitive and 81% specific for a viable pregnancy. Conclusion: Optimal serum estradiol levels are necessary for viability of pregnancy.